Survey Paper: Optimization and Monitoring of Kubernetes Cluster using Various Approaches - Hadikusuma, Ridwan Satrio; Lukas; Karel Octavianus Bachri (Politeknik Ganesha Medan, 2023)
This research compares different methods for optimizing and monitoring Kubernetes clusters. Three referenced journals are analyzed: